FACILITATING FUNCTIONS OF FIRST LANGUAGE (L1) IN THE CONVERSATION OF EFL LEARNERS - Aleksius, Madar; Goncalves, Sinartika Sara; Hornay, Priscilla Maria Asis (TELL - US JOURNAL, 2024)
This study was conducted to investigate the functions of L1 that appear in the conversations of EFL students and to find out the most common L1 function used by EFL students in facilitating conversation. This qualitative research was conducted by collecting the data by audio- and video-recording the participants’ conversations in when they were completing a communicative task called spot the differences. There were 20 EFL students involved in the study who took the Speaking for Everyday Communication course in the 2nd semester of the English Education study program at a private university in Kupang, Indonesia. The results of the study show that there were nine functions of the First Language (L1) used by the students.  From the highest to lowest in frequency of occurrence, the functions were sentence-internal code-switching, translation, giving instructions to the other classmates, confirmation, asking for instructions, asking for confirmation, personal petition, repetition, and direct appeal for help.  The employment of these nine L1 functions facilitates the smoothness of the EFL students’ conversations, hence making the conversations not cease. It was also found that all the students in this study used the Indonesian language as L1 in their conversation and that the use is generally caused by their struggle to use English as much as they can produce to speak.